English Language Education Students’ Intercultural Sensitivity in Cross Cultural Understanding Subject - Sugeng S susilo Adi (Universitas Veteran Bangun Nusantara, 2020)
Understanding cultural differences is one of the affective aspects in education. In English Language Education Program, Department of Language Education, Universitas Brawijaya, students are facilitated by learning the meaning of respecting cultural differences through the CCU subject course. This study aims at describing the intercultural sensitivity level of English education students who have taken the CCU course. It also tries to find out what factor that affects the students’ intercultural sensitivity level. This study used quantitative research design for measuring, assessing, and calculating the result based on numerical data. The questionnaires were distributed to 142 participants who from second, third, and fourth-year students and who have taken CCU course. The result of the study showed that 25% of students have ethnocentric level and 75% of ethno-relative level. The factor that affects both levels was the interaction engagement. It means that the students’ sensitivity level of cultural differences is very sufficient. However, there are still 25% students have no posttive perceprion about cultural differences. Therefor, faculty members still need to give innovation to the introduction of culture such as giving them insight into Indonesian culture.